Effects of Different Finishing Procedures on Surface Roughness of Hybrid CAD/CAM Materials - Akan, Ender; Colgecen, Ozlem; Meşe, Ibrahim Talha; Bağiş, Bora (Journal of Dentistry Indonesia, 2021)
Hybrid ceramics combine the beneficial properties of resin with the advantage of glass ceramics. However, there are limited study about on roughness properties of hybrid materials. Objective: To investigate of the effects of surface finishing methods on roughness of dental restorations made from hybrid CAD/CAM blocks. Methods: A total of 60 samples were produced (n=20) for three main material groups, two different hybrid ceramic (LAVA Ultimate and VITA Enamic) and a conventional glass ceramic (IPS e.max CAD). Each material group was divided into two subgroups (n=10). Ten samples were polished and 10 were glazed according to related manufacturer instructions. Surface roughness was measured with a surface profilometer. Data were statistically analysed using two-way ANOVA (p<0.05). Results: This study revealed that glazed surfaces were exhibited higher surface roughness values than polished surfaces in all materials (p<0.001). Minimum Ra values were belonged to Lava Ultimate polished group (Ra=0,07 μm) and maximum values were belonged to IPS e.max CAD glazed group (Ra=0,38 μm). Conclusion: Within the limitations of the present study, it may be suggested that finishing the hybrid ceramic restorations by mechanical polishing instead of glaze gives better clinical performance in regard to surface roughness.